2005
DOI: 10.1364/ol.30.002095
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimaging with a compact extreme-ultraviolet laser

Abstract: Images with a spatial resolution of 120-150 nm were obtained with 46.9 nm light from a compact capillarydischarge laser by use of the combination of a Sc-Si multilayer-coated Schwarzschild condenser and a freestanding imaging zone plate. The results are relevant to the development of compact extreme-ultraviolet laser-based imaging tools for nanoscience and nanotechnology. © 2005 Optical Society of America OCIS codes: 180.7460, 110.7440, 140.7240. Rapid progress in nanotechnology and nanoscience creates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Recently different approaches have emerged due to the development of smaller scale short-wavelength sources such as HHG [3], EUV lasers [4] and incoherent laser plasma-based sources [5] that have been successfully used for sub-micrometer resolution imaging. Using radiation from a table-top capillary discharge EUV laser images were obtained with a spatial resolution of 120-150 nm [6]. k = 13.2 nm wavelength radiation from Ni-like cadmium EUV laser allowed for a sub-38 nm resolution nano-imaging [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently different approaches have emerged due to the development of smaller scale short-wavelength sources such as HHG [3], EUV lasers [4] and incoherent laser plasma-based sources [5] that have been successfully used for sub-micrometer resolution imaging. Using radiation from a table-top capillary discharge EUV laser images were obtained with a spatial resolution of 120-150 nm [6]. k = 13.2 nm wavelength radiation from Ni-like cadmium EUV laser allowed for a sub-38 nm resolution nano-imaging [7].…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction limit of UV lights itself is down to 100 nm without a near-field probe. It has been reported that a compact capillary discharge UV laser can realize an imaging with a spatial resolution of 120-150 nm [86,87].…”
Section: Near-field Experiments In Thz Regionmentioning
confidence: 99%
“…Since the '90s, significant efforts were made to bring technical capabilities of synchrotron-based microscopes to the development of compact sources [1]- [8], because that the small size and versatility of compact microscopy system offers the possibility to perform imaging experiments, previously restricted to large-scale facilities, in university laboratories. It was already demonstrated that spatial resolution can be increased in nanoscale imaging systems employing short wavelength radiation such as soft X-ray (SXR) [9].…”
Section: Introductionmentioning
confidence: 99%